Foundations of Integrity: Good Corporate Governance in the Real Estate Sector – A Systematic Review - Nurfauzia, Fathima; Widiyati, Dian; Septiawan, Andhika Yusuf (Dinasti International Journal of Economics, Finance & Accounting, 2026)
Good Corporate Governance refers to the sound management practices adopted by companies to ensure transparency, accountability, and sustainability. This study seeks to examine how good corporate governance has been implemented in property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the period 2016–2024. The research employs a Systematic Literature Review (SLR) methodology, guided by the PRISMA Framework and utilizing a qualitative approach. The findings reveal that the application of good corporate governance has a significant impact on firm value, financial outcomes, and overall organizational performance within the property and real estate industry. This study is expected to support policy development and strategic decision-making aimed at enhancing the effectiveness of corporate governance practices in the sector.